Expectant mothers' experiences with lay doulas in maternity units of hospitals in impoverished areas of Iran: A qualitative study - Ameneh Safarzadeh; Vida Shafipour; AliReza Salar (Wolters Kluwer Medknow Publications, 2018)
Background: Qualitative research methods can help investigators ascertain the depth of people's needs and their perceptions. This study was designed to describe mothers' experiences and perceptions of lay doula services during labor and delivery. Materials and Methods: This study was conducted using a qualitative approach and conventional procedures of content analysis. The participants consisted of 13 nulliparous women at three hospitals affiliated with Zahedan University of Medical Sciences in 2016. Data were collected using face-to-face semi-structured interviews. Purposive sampling continued until data saturation was ensured. All interviews were tape-recorded and transcribed in verbatim. Results: Participants' experiences were categorized into 11 subthemes and five major themes including (1) achieving self-esteem and empowerment, (2) more trust in God, (3) promoting mental health of the mother, (4) willingness toward normal childbirth, and (5) lay doula as a listener and perceiver. Conclusions: In our study, the mothers evaluated the presence of a lay companion as an effective helper during childbirth and someone who promoted a remarkable willing toward normal childbirth. Healthcare professionals must be cognizant of the needs, values, beliefs, preferences, and emotional well-being of disadvantaged women during labor and delivery in poverty-stricken areas of Iran. Also, this study highlighted that it is important to include the perspective of support persons (such as husbands) in research design of future studies.